Unlocking the Potential of Less-Stabilized Carbenes in Chemical Synthesis: Chromium-Catalyzed Asymmetric Cyclopropanation - Qiqige, Qiqige; Wang, Zhaobin (Synlett, 2025)
Chiral cyclopropanes are crucial structural motifs in pharmaceuticals and valuable building blocks in organic synthesis. Traditional access via diazo compounds is often hampered by the instability of precursors for nonstabilized carbenes. Our group has focused on harnessing earth-abundant chromium to catalyze asymmetric cyclopropanations using readily available gem-dihaloalkanes as robust carbene surrogates. This article details our journey, from the initial development of a highly diastereo- and enantioselective cyclopropanation of gem-dihaloalkanes and terminal olefins to a more advanced system employing α-boryl and α-silyl dibromomethanes. This latter work enabled the synthesis of complex cyclopropanes with three contiguous stereocenters and led to the elucidation of a Cr(II)-based metalloradical catalytic pathway. These studies collectively showcase the power of chromium catalysis to unlock novel reactivity and provide stereo-controlled access to a diverse range of valuable chiral cyclopropanes.
Keywords: Asymmetric cyclopropanation; Chromium catalysis; gem-Dihaloalkanes; Nonstabilized carbenes; Metalloradical catalysis; Chiral cyclopropanes